PSYCHOLOGICAL FEATURES OF HARDINESS MANIFESTATION IN ADOLESCENCE - Фролова, Наталія Вікторівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The question of preserving psychological well-being in today’s world with its globalization is becoming actual and important. Person’s successful functioning is impossible without understanding of its hardiness that is the resource development, which contributes to its preservation in the time of crisis andchanging environment and the factors inflencing that process as well. Finding out the ways of its formation especially in adolescence is an important issue nowadays.Objecive of the study is to investigate the phenomenon of hardiness and the factors that inflences it in adolescence Method: theoretical (analysis and generalization of the theoretical approaches to the personality assessment); empirical; mathematical methods of elate processing: correlation and regression analysis; data interpretation (analysis, synthesis, systematization of data).Sumple 60 adolescents aged 13-14 years, 32 female and 28 male among them.Results It has been found out that hardiness has directly proportional correlation with the following disposition features - positive attitude (r = 0,395, p=0,01); psychological well-being(r = 0,512, p= 0,01 ); meaningfulness of life (r = 0,473, p=0,01); autonomy(r = 0,473, p=0,01) and there is no correlation between hardiness and such disposition features as extraversion and self perception.The regression analysis has let point out the main predictors of hardiness effectiveness. Meaningfulness of life (beta=0,394) and autonomy (beta=0,396) inflence the process successfully in adolescence.Conclusion The major results can be summarized in the following way: the successful formation of hardiness has been determined with the number of disposition features: positive attitude, psychological wellbeing, meaningfulness of life, autonomy. It has been proved that meaningfulness of life and autonomy are the predictors of hardiness effectiveness in adolescence